Transformational Leadership and Turnover Intention : The Mediating Role Of Employee Engagement - Saskia Tri Adella; Chici Andriani (Human Resource Management Studies, 2023)
This research aims to analyze: (1) The influence of transformational leadership on turnover intention among employees of Bank Nagari, Padang City Head Office. (2) The influence of transformational leadership on Employee Engagement among Bank Nagari employees, Padang City Head Office. (3) The influence of Employee Engagement on Turnover Intention among Bank Nagari employees, Padang City Head Office. (4) The Influence of Transformational Leadership on Turnover Intention among Bank Nagari Employees, Padang City Head Office through Employee Engagement. This research is causal research. The population in this study were all employees of Bank Nagari, Padang City Head Office, totaling 240 people. Meanwhile, the number of samples used in this research was determined using the Slovin formula so that the sample size was 150 people. The analysis technique used is SmartPLS4 software. The results of this research show that: (1) Transformational Leadership has a negative and significant effect on Turnover Intention among Bank Nagari employees, Padang City Head Office. (2) Transformational Leadership has a positive and significant effect on Employee Engagement among Bank Nagari employees, Padang City Head Office. (3) Employee Engagement has a negative and significant influence on Turnover Intention among Bank Nagari employees, Padang City Head Office. (4) Transformational Leadership has a negative and significant effect on Turnover Intention with Employee Engagement as a mediating variable for Bank Nagari employees, Padang City Head Office